ORIENTASI PEMIKIRAN HUKUM BERKARAKTER KEINDONESIAAN DALAM PERSPEKTIF TEORI HUKUM - Arif Hidayat (Jurnal Pembaharuan Hukum, 2015)
This legal research is exploratory to examine the orientation of legal thought characterless Indonesia in the perspective of legal theory. Through conceptual approaches, normative-doctrinal research using qualitative methods of critical analysis. The study concluded that the theorization of law in Indonesia is not only adopted the thinking with Indonesia setting, but consider the legal relationships that are global as the ingredients thought to develop a theory of the laws of Indonesia in the future. Building a legal theory in Indonesia is an intelectual activity requiring deep thought with a holistic perspective. Thus, growth and development of Indonesia legal theory must pay attention to the fact, that the law is a part of Indonesian culture. Postulate progressive law is very relevant into bid middle path, where the progressive law it should be pro-people and pro-justice, and aims to deliver human well-being and happiness.